Ace-Spire Your MUET: English Club's MUET preparation webinar / Muhammad Aiman Abdul Halim and Nazima Versay Kudus - Abdul Halim, Muhammad Aiman; Kudus, Nazima Versay (Academy of Language Studies, 2023)
On 10th June 2023, the English Language Club of UiTM Cawangan Pulau Pinang (UiTMCPP) hosted an intensive Malaysian University English Test (MUET) webinar under the name "Ace-Spire Your MUET." This programme aimed to guide and motivate students gearing up for their imminent MUET examinations, providing them with essential tips and strategies to ace MUET questions while nurturing their analytical skills. Despite postponement of nearly two months from its original date, this 3-hour webinar witnessed the enthusiastic participation of 17 UiTM students and 26 Form Six students from other esteemed institutions. Guided by two Akademi Pengajian Bahasa (APB) lecturers as programme advisors, this initiative was driven solely by passion and collaboration, devoid of any university budget. In a collaboration with Penerbit Ehsan, the English Language Club had successfully provided participants with textbooks, webinar platform, and the expertise of an acclaimed MUET examiner, Mr. Choo Wan Yat. As the author of ACE MUET, along with a repertoire of other esteemed workbooks and textbooks, Mr. Choo is a highly sought-after speaker in the MUET community. His expertise shone as he delved into MUET's Writing and Reading components, endowing participants with invaluable insights aligned with the latest syllabus based on the Common European Framework of Reference for Languages (CEFR).